2004
DOI: 10.1159/000077355
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-3-Mediated Apoptosis of Human Eosinophils by the Tissue-Invading Helminth <i>Paragonimus westermani</i>

Abstract: Background: Eosinophils are important cells in host immunity to infections by parasitic worms. Tissue-invasive helminthic parasites have been known to induce apoptosis of immune cells for their successful establishment in vivo. We have previously found that high doses of excretory-secreted products (ESP) secreted by lung fluke Paragonimus westermani newly excysted metacercariae (PwNEM), which cause pulmonary or extrapulmonary paragonimiasis in human beings, accelerate eosinophil cell death. However, little is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 31 publications
0
27
0
1
Order By: Relevance
“…The ESP produced by PwNEM was recently found to rapidly induce a direct time-and concentration-dependent increase in the rate of constitutive apoptosis in normal human eosinophils [16]. Moreover, eosinophil apoptosis by the ESP was shown to be mediated by activation of caspase-3 [17]. In addition, we observed that 10 μ g/ ml of the 27 kDa CP rapidly induced phosphatidylserine externalization on the cell surface of human eosinophils (data not shown).…”
mentioning
confidence: 64%
“…The ESP produced by PwNEM was recently found to rapidly induce a direct time-and concentration-dependent increase in the rate of constitutive apoptosis in normal human eosinophils [16]. Moreover, eosinophil apoptosis by the ESP was shown to be mediated by activation of caspase-3 [17]. In addition, we observed that 10 μ g/ ml of the 27 kDa CP rapidly induced phosphatidylserine externalization on the cell surface of human eosinophils (data not shown).…”
mentioning
confidence: 64%
“…In our experiments, we found an increase in caspase-3 activity in peritoneal cells from infected mice at several time points after infection. Likewise, Min et al (2004) reported activated caspase 3 in eosinophils incubated with Paragonimus westermani excretory-secretory products. In these cells, we also observed chromatin condensation, strangling, and nuclear fragmentation by performing electron microscopy studies Fig.…”
Section: Discussionmentioning
confidence: 93%
“…The parasite produces products that result in what has been termed "a zone of immune privilege" (17,116). This occurs, in part, as the result of the action of 27-and 28-kDa enzymes released from the parasite that cleave human immunoglobulin G (IgG) (17,42).…”
Section: Life Cyclementioning
confidence: 99%
“…The degradation of IgG in turn results in the diminution of IgG-induced eosinophil degranulation and production/release of superoxide (160). Eosinophils become apoptotic in response to worm excretory/ secretory products, which in turn results in a substantial downregulation of the local inflammatory response (116).…”
Section: Life Cyclementioning
confidence: 99%